Retrospective study of sports-related maxillofacial fractures in a Brazilian trauma care center - Julia Souza Ribeiro-; Vinícius Paes de Assis Santos; João Gualberto Cerqueira Luz (Universidade Estadual de Campinas, 2021)
Aim: Maxillofacial fractures occur frequently in the general population, and sports-related fractures represent some of these cases. However, few studies have been carried out in Brazilian populations aimed at sports-related maxillofacial fractures. This study assessed the demographic and fracture characteristics of patients with sports-related maxillofacial fractures who were seen at a Brazilian trauma care center. Methods: Medical records of patients with a history of sports-related maxillofacial fractures treated between January 2018 and December 2019 were retrospectively evaluated. Personal data, fracture characteristics, sport type, treatment performed and need for hospitalization were collected. The data were subjected to statistical analyses with likelihood ratio test using the Statistical Package for Social Sciences (SPSS) 25.0 (p ≤ 0.050). Results: Forty cases (4.96% of the total) of facial fractures were included. The mean age was 24.9 (± 9.8) years, with a predominance of males (92.5%). The use of protective equipment was rare. The most frequently involved sport modality was soccer (47.5%), followed by cycling (27.5%). The most frequent fracture location was nose (45%), followed by mandible (25%) and zygomatic complex (17.5%). Soccer was responsible for most nose fractures (61.1%), while cycling caused the majority of mandibular fractures (60%). Conservative treatment predominated (60%). There was only a significant difference between fracture location and the need for hospitalization (p = 0.021). Conclusion: Patients with sportsrelated maxillofacial fractures were typically young adult males, the injury was more often located in the nose and mandible and related to soccer or cycling. The use of protective equipment must be reinforced.